Bimbingan Teknis Pupuk Organik Cair untuk Meningkatkan Produksi Karet Rakyat di Payaraman Barat Kabupaten Ogan Ilir - Setyawan, Dwi; Budianta, Dedik; Warsito, Warsito; Priatna, Satria Jaya (PRIMA: Journal of Community Empowering and Services, 2022)
Technical Assistance Using Liquid Organic Fertilizer for Improving Small-Scale Rubber Production in Payaraman Barat, Kabupaten Ogan Ilir. Liquid organic fertilizer (POC) is getting more attention from users (researchers, farmers, planters and others) because of the various advantages it has. Its manufacture is not too difficult and can use local raw materials ( agricultural waste, market waste or potential household organic waste). One of the advantages is that it can reduce the cost of fertilization. POC can be used to improve soil fertility and it is hoped that in the end it will be able to increase the productivity of rubber plants. This community service activity aims to provide technical guidance on how to make POC in a simple way and then apply it to rubber plants, accompanied by sanitation of the garden environment by cleaning weeds. There are four waste materials or plant materials used to make POC, namely pineapple peel waste, papaya fruit, banana peel and water hyacinth. The material is fermented in a simple reactor made of a gallon or bucket of used paint that is perforated and fitted with a faucet. The fermentation process is assisted by black soldier flies which will come into the reactor by themselves. After two weeks it will begin to produce fermented liquid. After four weeks the liquid is dried in the sun until it turns dark brown and is ready to use. In this activity, doses of 10, 20, 30 or 40 mL of POC were dissolved into 1 liter. The results of the socialization showed that 15 members of the farmer group did not know about POC and were very interested in using it. Preliminary data (n=30) showed a fairly large variation in sap production (59.7±48.6 grams/tree). Some rubber stems do not release sap, and the highest can reach 142.9 grams/tree with an average of 41 to 83 grams/tree. The collection of results is carried out every week according to latex sales. After 4 weeks of application of POC pineapple peel production can reach 165 to 470 grams/tree.